An FPGA-Based Parallel Distributed Arithmetic Implementation of the 1-D Discrete Wavelet Transform - M. Al-Haj, A. (Informatica)
An FPGA-Based Parallel Distributed Arithmetic Implementation of the 1-D Discrete Wavelet Transform